Endoscopic transsphenoidal surgery and Haddad nasoseptal flap of Rathke’s cleft cysts - Fadjar Perkasa, Muhammad (Gaceta Médica de Caracas, 2023)
Introduction: Rathke’s cleft cysts (RCC) grow formed from remnants of the embryologic Rathke’s pouch and are often found incidentally in the sellar or suprasellar region. These lesions are usually asymptomatic in most people. However, as the cyst progressively enlarges, they may develop symptoms typical of RCC, including headache, vision loss, and endocrine dysfunction. The diagnosis procedure involves an MRI scan of the pituitary gland. The endoscopic transsphenoidal approach has become the most common surgical approach to treat RCC. In the last 15 years, endonasal endoscopy has been widely used in the surgical management of these lesions. Case report: A 58-year-old Asian woman was reported mainly with a complaint of headache that had increased over the last two months, occasional nausea and vomiting, and blurred vision experienced for 1 month.